Psychological Antecedents of Retirement Planning: A Systematic Review - Kerry, Matthew J. (Frontiers in Psychology, 2018)
As workforce aging continues through the next decade, the number of persons who will retire from long-held jobs and careers will increase. In recent years, researchers across disciplines of psychology have focused attention on the impact of the retirement process on post-retirement adjustment and well-being. One area that has received attention from investigators in both psychology and economics pertains to the impact of retirement planning on the retirement decision and post-retirement adjustment. The objective of the current review is twohreefold. The first goal is to review the literature on retirement planning with attention to past conceptualizations and current theoretical specifications. Second, empirical work investigating the psychological antecedents of retirement planning is reviewed. The primary conclusion reached from this review is that, conceptually, retirement planning continues to be poorly delineated and, thereby, narrowly investigated. Empirically, cognitive antecedents of retirement planning continue to figure prominently in both workplace and retirement researches. The boundary conditions of retirement planning, as well as alternative mechanisms for adult wellbeing, are discussed. Specifically, retirement planning’s meaning amidst increasing job mobility and longer life expectancies are identified as two complementary areas for future empirical integration of work - retirement research domains.